Earth System Science and Education: From Foundational Thoughts to Geoethical Engagement in the Anthropocene - Tiago Ribeiro; Clara Vasconcelos (Geosciences)
Understanding Earth as a complex, dynamic, and interconnected system is crucial to addressing the contemporary environmental challenges intensified in the Anthropocene. This article reviews foundational Earth System Science (ESS) developments, emphasizing its transdisciplinary nature and highlighting how it has evolved to address critical issues like climate change, biodiversity loss, and sustainability. Concurrently, Earth System Education (ESE) has emerged as an educational approach to foster holistic a understanding, environmental insights, and geoethical values among citizens. Integrating geoethics into ESE equips citizens with scientific knowledge and the ethical reasoning necessary for responsible decision making and proactive engagement in sustainability efforts. This article identifies system thinking and environmental insight as the key competencies that enable individuals to appreciate the interconnectedness of Earth’s subsystems and humanity’s role within this complex framework. This study advocates for embedding a holistic and geoethical view of the Earth system into formal and non-formal education, promoting inclusive, participatory, and action-oriented learning experiences. This educational shift is essential for empowering citizens to effectively address the environmental, social, and economic dimensions of sustainability, thereby fostering resilient, informed, and ethically responsible global citizenship in the Anthropocene.